FLAG-IDA, Possible Breakthrough in Treatment of Refractory Acute Myeloid Leukemia in the Context of Hematopoietic Stem Cell Transplantation: Single Center Experience - Chadievski, Lazar; Stavric, Sonja Genadieva; Veljanovska, Aleksandra Pivkova; Stojanoski, Zlate; Miloska, Dijana; Cevreska, Lidija; Georgievski, Borche (Walter de Gruyter GmbH / Македонско лекарско друштво = Macedonian medical association, 2017)
Abstract Introduction. Acute myeloid leukemia (AML) represents an entity well defined among the hematological malignnant diseases from diagnostic and therapeutic point of view. Still, big concern remains for those patients where the induction therapy fails. Classified in the group of refractory AML these patients are with poor prognosis. There are numerous attempts in providing the best surviving results by administration of appropriate therapy. Our center presents its experience in treating patients with refractory AML by administration of FLAG-Ida regimen, followed by hematopoietic stem cell transplanttation, autologous or allogeneic, depending on the availability of HLA matched sibling donor of hematopoietic stem cells. Methods. In patients with refractory AML, administering FLAG-Ida chemotherapy we have achieved complete remission in 22 patients (47%). Average age of the treated group of patients was 36.6 years (17-53). All of them proceeded to high-dose chemotherapy and underwent hematopoietic stem cell transplantation (HSCT). We performed autologous HSCT in 13 patients, and allogeneic HSCT in 9 patients. Median time to HSCT was 6.6 months (4-10), and in most of the patients we used myeloablative conditioning (MAC). Results. The disease-free survival in our group of patients is 74 months (22-148). The longest overall survival was 148 months and was registered in a patient with allogeneic sibling HSCT. We can conclude that FLAG-Ida regimen is an appropriate and suitable salvage chemotherapy protocol for patients with refractory AML especially when it is used in the context of preparation for HSCT.
FLAG-IDA протоколот - можен избор на лекување рефракторна акутна миелоидна леукемија, во контекст на транспалнтацијата на хематопетски матични клетки